A Job Ladder Model with Stochastic Employment Opportunities - Jake Bradley; Axel Gottfries (Institute of Labor Economics (IZA), 2018)
We set up a model with on-the-job search in which firms infrequently post vacancies for which workers occasionally apply. The model nests the standard job ladder and stock-flow models as special cases while remaining analytically tractable and easy to estimate from standard panel data sets. Structurally estimating the model, the parameters are significantly different from the stock-flow or the job ladder model. Further, the estimated parameters governing workers search behavior are found to be consistent with recent survey evidence documented in Faberman et al. (2016). The search behavior implied by the standard job ladder model significantly understates the search option associated with employment (and thus underestimates the replacement ratio). Finally, the standard model is unable to generate the decline in the job finding rate and starting wage with duration of unemployment, both of which are present in our data.
Keywords: J31; J64; 330; on-the-job search; wage dispersion; wage posting; stock-flow